Intellectual Capital and Bank Profitability Nexus: Evidence From Gulf Cooperation Council Countries - Osman, Zaroug; Yilmaz, Ilker (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This article presents novel and fresh empirical evidence on the relationship between intellectual capital and bank profitability and reports the results for the whole sample as well as at country breakdown. Research Objectives: Using a dataset of 60 banks from GCC countries between 2008 and 2022, the article investigates the association between intellectual capital and bank profitability by implementing M-VAIC. Research Methods: We developed two models in which profitability ratios are the dependent variables and the M-VAIC components are the independent variables and ran pooled OLS and panel regressions. Empirical Result: The study’s findings showed that while structural capital efficiency has a negative influence on bank profitability, other components have a positive impact on bank profitability. The signs and the significance levels at the country details do not show essential differences. Implications: The study’s results will have significant implications on how bank managers and policymakers invest and manage intellectual capital. The study offered an original contribution to the literature by presenting fresh empirical evidence from GCC countries for a reasonably long period. JEL Classification: E22, G21, O34, L25